Three new species of Liparis s.l. (Orchidaceae: Malaxideae) from Southwest China based on morphological characters and phylogenetic evidence - Ji-Dong Ya (KeAi Communications Co., Ltd., 2021)
Liparis aureolabella and L. mengziensis, two new species from the karst region of southwestern China, and L. bingzhongluoensis, a new species from montane region in Yunnan, are described and illustrated. L. aureolabella is easily distinguished from its relatives by having abaxially purple leave with purple reticulate veins prominent adaxially, a lip auriculate at base, and falcate-lanceolate pollinia. Liparis mengziensis is closely related to L. petiolata and L. auriculata, but differs from them by having an ovate to broadly ovate leaf, purple lip and apex connate along the margins. Liparis bingzhongluoensis is similar to Liparis nanlingensis, but the new species is characterized by having a lip with two transparent ridges on its disc, longitudinally concave basal callus and triangular column wings. Phylogenetic analyses based on nuclear ribosomal ITS and plastid matK sequences showed that L. aureolabella and L. mengziensis are nested with L. petiolata or L. auriculata in a monophyletic clade. L. bingzhongluoensis is sister to a clade formed by L. nanlingensis, L. tsii, L. sasakii and L. krameri. Moreover, morphological comparisons strongly support that the three species as separated species newly to science.